Richness of Butterflies Species at Three Habitat Type in Karimunjawa Island Central Java - Wisnu Bayu Murti; Nugroho Edi Kartijono; Margareta Rahayuningsih (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2016)
The purpose of this research was to determine the species richness of butterflies on three type habitats in Karimunjawa Island. The research was conducted in May-October 2016. The research location on the island of Karimunjawa in three habitat types, edge of lowland tropical forest, paddy fields and settlements. Sampling was conducted four times of observation on each habitat type and Point Count Method. Identification species of butterflies use a guidebook Serangga Taman Nasional Gunung Halimun Jawa Bagian Barat and analyzed by uses Margalef Index. The results showed total 49 species of butterflies from 1402 individual (5 Family) was found in three types of habitat. Butterfly species richness highest in a edge habitat of lowland tropical forest (5.9), settlements (5.2), and paddy fields (4.6). ©2016 JNSMR UIN Walisongo. All rights reserved.